A nifty fix for published distribution statistics: Simplified distribution-free statistical inference - Charles M. Beach (Queen's University, Department of Economics, 2021)
This paper applies the tool box measures of disaggregative income inequality characterization and the statistical methodology of Beach (2021) to percentile-based distribution statistics such as quintile income shares and decile means typically published by official statistical agencies. It derives standard error formulas for those measures which are distributionfree and easy to implement. The approach is illustrated with Canadian Labour Force Survey data over 1997-2015. It is found that widely shared real earnings gains were experienced over this period, but that the gains were very unevenly shared with middle-class workers losing out relatively and top earners having highly statistically significant earnings gains.
Keywords: C12; C46; D31; D63; 330; income inequality; inequality inference; statistical inference